Comparison between Shear Bond Strength of Er:YAG and Er,Cr:YSGG Lasers-Assisted Dentinal Adhesion of Self-Adhering Resin Composite: An Ex Vivo Study - Paul Nahas; Samir Nammour; Elie Gerges; Toni Zeinoun (MDPI AG, 2020)
(1) Background: Bonding composite to tooth structure is still evolving with a substitute for phosphoric acid being the main challenge. Lately, a self-adhering composite (SAC) was developed, promising to simplify bonding to tooth structure. Unfortunately, retention especially to dentin, was not as good as the gold standard three steps bonding system. During the last 2 decades, lasers were used to enhance shear bond strength of composite to tooth structure. However, the literature provided limited information regarding laser efficiency in the immediate, as well as the long term, adhesion success of SACs to dentin. The purpose of our study was to define the optimal irradiation conditions to improve the adhesion of self-adhering flowable resin composite to dentin exposed to Er:YAG and Er,Cr:YSGG laser irradiation. (2) Methods: Seventy-two freshly extracted human third molars, prepared to have flat dentinal surfaces, were randomly divided into three groups (n = 24) including a control group (Group 1) in which dentin was left without laser irradiation. The other two groups (Group 2 and 3) received standardized irradiation at a speed of 1 mm/second with Er:YAG (60 mJ; SSP mode = 50 μs; 10 Hz; fluency of 9.4 J/cm2; beam diameter: 0.9 mm; air 6 mL/min; and water 4 mL/min), and Er,Cr:YSGG: 1.5 W; fluency of 17.8 J/cm2; turbo handpiece with MX5 short insert; 20 Hz under air/water spray (65% air, 55% water). Self-adhering flowable resin was applied to dentin in all groups. Half of the specimens were stored in water for 24 h while the other half underwent 3000 thermal cycles. Later, all specimens received a shear bond strength test. Fracture observation was done first under a stereomicroscope then by using a scanning electron microscope. (3) Results: The mean values of shear bond strength for both laser-treated dentin groups (Er:YAG laser: 13.10 ± 1.291, and Er,Cr:YSGG: 14.04 ± 5.233) were higher than in the control group 1 (8.355 ± 2.297) before thermocycling. After thermocycling, shear bond strength decreased in all groups as follows: 10.03 ± 1.503, 10.53 ± 2.631, and 02.75 ± 1.583 for Er:YAG, Er,Cr:YSGG, and nonirradiated dentin, respectively. Shear bond strength values showed a significant difference between the control group (Group 1) and both lasers groups (Group 2 and 3). Statistical analysis of stereomicroscope observation revealed no significant difference between laser irradiation and failure mode (p < 0.136). SEM observation of the dentin surface in both laser-irradiated groups showed opened tubules, absence of smear layer as well as an increase of resin infiltration into dentinal tubules. (4) Conclusion: Er:YAG and Er,Cr:YSGG lasers enhance self-adhering flowable resin shear bond strength values and improve its longevity by eliminating the smear layer, opening dentinal tubules and increasing resin infiltration into the microstructure.